Effects of deferment periods and cutting intervals on forage production and seed yield of white clover cv. Guaíba S1 - Andrade, José Luiz Rocha; Nabinger, Carlos; Paim, Nilton R. (Pesquisa Agropecuaria Brasileira, 2014)
This research has been carried out at the Estação Experimental Agronômica of UFRGS, in Eldorado do Sul, RS, Brazil, to determine the effects of several deferment periods and cutting frequencies on forage dry matter yields and seed yield components of white clover (Trifolium repens L.) cv. Guaíba S1. Two cutting frequencies (four and eight-week intervals) as well as five deferment periods (early September, late September, late October, late November and late December) were used in a split-plot experimental design, with five repetitions, in which deferment periods were the main plots and cutting frequencies the subplots. Late deferment (end of December) revealed the lowest seed production as well as the decrease of all seed yield components. The best results to both characteristics were obtained in early deferment periods. On the other hand, the 8 week-cutting frequency produced the highest seed weight, stolon density and stolon length whereas the 4 week-cutting frequency gave rise to the highest flower head number/stolon.